Case Report: I want more olanzapine: pharmacogenetic insights into a patient's preference for high-dose olanzapine - Liam Korošec Hudnik; Ivo Kosmačin; Tanja Blagus; Vita Dolžan; Jurij Bon; Jurij Bon; Milica Pjevac; Milica Pjevac (Frontiers in Psychiatry)
Olanzapine is an effective antipsychotic agent, but its metabolism shows considerable interindividual variability. We present a case of a patient with treatment-resistant schizophrenia who consistently required and preferred high-dose olanzapine (40–60 mg/day) for symptom control. The patient reported improved motivation and energy following the reduction of adjunctive antipsychotics.MethodsThe patient’s clinical course and treatment history were retrospectively reviewed. Plasma olanzapine levels were measured to assess systemic drug exposure, and pharmacogenetic testing for CYP1A2, CYP2D6, CYP3A4, and CYP3A5 polymorphisms was performed using PCR-based genotyping.ResultsGenotyping revealed CYP1A2 -163AA genotype, consistent with an ultrarapid metabolizer phenotype, and CYP2D6 *1/*9 genotype, indicating slightly reduced but overall normal enzyme activity. At 40 mg/day, the olanzapine trough level was 51 ng/mL—lower than expected for a non-smoker—suggesting enhanced metabolic clearance. This pharmacokinetic profile, shaped by genetic predisposition and smoking, likely necessitated higher olanzapine doses to reach therapeutic levels. Discontinuation of haloperidol and risperidone was associated with improved subjective energy and engagement.ConclusionThis case illustrates how pharmacogenetic variability may influence antipsychotic efficacy and tolerability. The patient’s ultrarapid CYP1A2 metabolism and smoking status likely reduced olanzapine exposure, warranting higher doses for clinical response. Pharmacogenetic profiling may provide valuable insights into individual treatment needs and support more personalized approaches in complex psychiatric cases.